Tasmannia lanceolata (Poir.) A.C.Sm. Pepperberry Extracts Inhibit the Growth of the Pharyngitis Causing Pathogen Streptococcus pyogenes - Winnett, Veronica; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Streptococcus pyogenes is a gram positive pathogenic bacterium which causes a variety of diseases including streptococcal pharyngitis, impetigo and rheumatic heart disease, depending on which tissue it infects. Tasmannia lanceolata (Poir.) A.C.Sm. pepperberries were used therapeutically by the first Australians, including for the treatmenbt of bacterial infections. This study focuses on the growth inhibitory activity of T. lanceolata pepperberry extracts against S. pyogenes. Materials and Methods: Solvent extracts were prepared from Tasmannia lanceolata pepperberries using solvents of varying polarity. The extracts were investigated by disc diffusion assay for the ability to inhibit the growth of S. pyogenes. MIC values were subsequently quantified by both solid-phase and liquid dilution MIC assays. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: The methanolic, aqueous and ethyl acetate T. lanceolata pepperberry extracts displayed noteworthy antibacterial activity in the disc diffusion and liquid dilution bioassays against S. pyogenes. The methanolic extract was particularly potent, with an LD MIC value of 782 µg/mL recorded. The aqueous and ethyl acetate T. lanceolata pepperberry extracts also displayed noteworthy growth inhibitory activity of S. pyogenes, albeit with substantially higher LD MIC values (1375 and 1125 µg/mL respectively). All extracts were determined to be non-toxic in the Artemia nauplii bioassays, with LC50 values substantially >1000 µg/mL. Conclusion: The noteworthy growth inhibitory bioactivity of the methanolic, aqueous and ethyl acetate T. lanceolata pepperberry extracts against S. pyogenes demonstrates their potential for the treatment and prevention of pharyngitis, impetigo and rheumatic heart disease. All extracts were nontoxic indicating their safety for therapeutic use.
Keywords: Winteraceae; Australian Plants; Mountain Pepperberry; Tasmanian Pepper; Pharyngitis; Impetigo; Rheumatic Heart Disease; Antibacterial Activity